(untitled) (Journal of Computational Mathematics, 2018)
In this paper, we consider the linear elasticity problem based on the Hellinger-Reissner variational principle. An O(h^2) order superclose property for the stress and displacement and a global superconvergence result of the displacement are established by employing a Clément interpolation, an integral identity and appropriate postprocessing techniques.